2016
DOI: 10.1007/s11682-016-9602-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in brain white matter in adolescents with 22q11.2 deletion syndrome and psychotic symptoms

Abstract: Background 22q11.2 Deletion Syndrome (22q11DS) is considered to be a promising cohort to explore biomarkers of schizophrenia risk based on a 30% probability of developing schizophrenia in adulthood. In this study, we investigated abnormalities in the microstructure of white matter in adolescents with 22q11DS and their specificity to prodromal symptoms of schizophrenia. Methods Diffusion Magnetic Resonance Imaging (dMRI) data were acquired from 50 subjects with 22q11DS (9 with and 41 without prodromal psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…WM differences associated with psychosis are of interest in 22q11DS. Psychotic symptoms in 22q11DS have been associated with higher FA and lower WM diffusivities, but not always in the same regions across studies [22,25,30,31,33,34]. In addition, there is variability in deletion breakpoints; 85-90% of individuals with the deletion have a~3 Mb (A-D) deletion, containing 46 protein-coding genes, whereas~10% of cases have a nested 1.5 Mb (A-B) deletion [1].…”
Section: Introductionmentioning
confidence: 99%
“…WM differences associated with psychosis are of interest in 22q11DS. Psychotic symptoms in 22q11DS have been associated with higher FA and lower WM diffusivities, but not always in the same regions across studies [22,25,30,31,33,34]. In addition, there is variability in deletion breakpoints; 85-90% of individuals with the deletion have a~3 Mb (A-D) deletion, containing 46 protein-coding genes, whereas~10% of cases have a nested 1.5 Mb (A-B) deletion [1].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a recent review article, we concluded that higher symptoms severity is associated with altered long-range frontal connections ( 13 ). Fewer studies specifically investigated brain morphology and connectivity in 22q11DS patients with high psychotic symptoms compared to less symptomatic patients ( 14 21 ). The aim of this manuscript is to review evidence of specific alterations at the level of brain morphology and connectivity in patients with 22q11DS with a higher clinical risk to develop psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to disentangle which brain connectivity alterations are associated to psychosis, it is essential to compare patients with 22q11DS with different levels of symptoms severity. To date, only one study investigated structural connectivity differences in subgroups of patients with 22q11DS ( Kikinis et al, 2016 ). The authors compared adolescent patients with 22q11DS with high and low psychotic symptoms scores and showed altered white matter diffusivity in the most symptomatic patients ( Kikinis et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one study investigated structural connectivity differences in subgroups of patients with 22q11DS ( Kikinis et al, 2016 ). The authors compared adolescent patients with 22q11DS with high and low psychotic symptoms scores and showed altered white matter diffusivity in the most symptomatic patients ( Kikinis et al, 2016 ). However, this investigation was limited by the low number of patients included ( N = 9 patients with high symptoms severity).…”
Section: Introductionmentioning
confidence: 99%